The scenarios for the future of EU public policies: the perspective of the theory of public goods - Surdej, Aleksander (Economics and Business Review, 2014)
Starting from the economic theory of public goods the author builds a framework for an analysis of the ways European public goods are identified and provided. The specific aim of the paper is to discuss the criteria for designing an adequate institutional framework of the provision of public goods and to explain why there is a tendency for a misalignment between the citizens expectations and EU public policy outcomes. (original abstract)